Mental Health Status of Students in The Faculty of Public Health - Sribenja, Thanaporn; Chantawee, Thanyamai; Teekamkaset, Wasinee (Chalermkarnchana Academic Journal, 2022)
This research It is exploratory research. The objectives were (1) to study the mental health status of students at the Faculty of Public Health Sciences (2) to study concepts related to relationships that cause mental health problems (3) to study solutions to problems of students at the Faculty of Public Health Sciences. Lai Chalermkanjana. The sample group was 43 operators who analyzed the instrument. Ask for help from a statistical analysis of distributed data, which contains values ​​to answer questions. and fractional values ​​for standard samples. Analyze the relationship to the chi-square statistic. The study found that the mental health status was normal. It was found that the mental health status of the first-year students have a mental health condition 70.28 percent were normal, followed by mental health status of fourth year students. 56.47 percent of the mental health status of the second-year students had mental health status. 54.38 percent were normal and the mental health status of the third-year students had mental health status. as usual, 39.50 percent, respectively.